This sovereign land : a new vision for governing the West - Kemmis, Daniel, 1945- (Island Press, 2001)
"In This Sovereign Land, Daniel Kemmis offers a radical new proposal for keeping public lands public but shifting their jurisdiction from nation to region. Kemmis, a leading western Democrat and committed environmentalist, argues against those who wish to privatize the public lands. He offers a regional approach that takes into account natural topographical and ecological features, directed by local residents with a vested interest in ensuring the sustainability of their communities. In effect, Kemmis carries John Wesley Powell's recommendations to their logical conclusion."